Comparison and Applications of Multiplying 2 by 2 Matrices Using Strassen Algorithm in Python IDLE, Jupyter Notebook, and Colab - Gao, Shanzhen; Gao, Weizheng; Malomo, Olumide; Allagan, Julian D.; Eyob, Ephrem; Su, Jianning (2023 Congress in Computer Science, Computer Engineering, & Applied Computing (CSCE), 2023)
Even though the task of multiplying matrices appears to be rather straightforward, it can be quite challenging in practice. Many researchers have focused on how to effectively multiply two 2 by 2 matrices by applying Strassen Algorithm in the past 50 years. They worked on the complexity from both the mathematical and algorithmic points of view. In our paper, we will discuss the comparison of processing time in Python IDLE, Jupyter Notebook, and Colab from a practical point of view. Several open problems are then presented to challenge our readers.